A multilayer soil approach for seepage process analysis in earthen levees. Issue 3 (1st April 2022) - Bonaccorsi, Bianca; Moramarco, Tommaso; Noto, Leonardo Valerio; Barbetta, Silvia
Abstract: The analysis of seepage through earthen levees is fundamental to investigate the levee safety condition, since that the seepage phenomenon can often lead to piping causing the collapse of the levee (Saghaee et al., 2012). This work proposes a new approach for identifying the location of the saturation line through the earthen levee by using a multilayer soil approach that assumes the levee body and the levee foundation as two different layers, characterized by using a different hydraulic conductivity parameter. The main purpose is to investigate the difference in the predicted saturation line identified through the proposed method and the one based on the single layer analytical solution of the seepage flow suggested by Marchi (1961). On comparison of the saturation lines provided by two different approaches, the ratio between the river water head and the groundwater thickness or depth increases; allowing the determination of a ratio threshold above which the Marchi equation should no longer be applied. The proposed multilayer (levee and foundation) soil approach is also used to assess the seepage vulnerability of the methodology proposed by Barbetta et al. (2017). The results show that the differences between the seepage vulnerabilities evaluated using the multilayer approach and the single layer method are quite low. Although notably, significant modifications of the seepage probability are observed when the distance between the ground level and the groundwater table changes.